KOMPARASI PENDEKATAN SES DAN SMA UNTUK PREDIKSI HASIL PRODUKSI KELAPA SAWIT - Fahdrina, Jihan Aulia Putri; Anggraeni, Dewi; Santoso, Santoso (LPPM STMIK Royal Kisaran, 2025)
Abstract: Palm oil is a key commodity that requires accurate production planning to support budget and operational efficiency. PT Buana Sawit Indah, a company managing palm oil plantations, faces challenges in forecasting future production, necessitating a computerized forecasting system. This study aims to develop a forecasting system using the Single Exponential Smoothing (SES) and Single Moving Average (SMA) methods to predict palm oil production. The results indicate that both methods are effective; however, SMA with a Moving Average (MA) of 5 provides the best forecasting results, with a MAD of 165,941.64, an MSE of 65,823,372,491.27, and an MAPE of 15.66%, categorized as